PERAN KRUSIAL MANAJEMEN STRATEGI DALAM MENINGKATKAN KINERJA ORGANISASI PUBLIK - Sukmiridiyanto; Pitojo Budiono; Maulana Mukhlis (Journal Publicuho, 2024)
Strategic management is a crucial process involving the formulation, implementation, and evaluation of decisions to achieve an organization's long-term objectives. This research examines the role of strategic management in improving the performance of public organizations in Indonesia, focusing on a review of various strategic management approaches and practices, as well as the challenges of implementation in the public sector. The method used in this study is a literature review, sourcing from books, academic journals, articles, and other relevant materials related to the research topic. Findings from this literature review indicate that adapting to technology and employing participatory approaches are key to enhancing public organization performance. However, challenges such as bureaucracy and resistance to change remain significant obstacles. With the right approach, public organizations in Indonesia can overcome these challenges and achieve better performance in serving the community.